Detection of atomoxetine and its metabolites in the urine by thin-layer chromatography and mass spectrometry - S. A. Karpushyna; S. V. Baiurka; T. O. Tomarovska (Zaporozhye State Medical University, 2022)
The aim of the study was the detection of atomoxetine and its biotransformation products in the urine under TLC screening conditions and identification of the metabolites using mass spectrometry method. Materials and methods. The volunteer's urine samples after taking a single therapeutic dose of atomoxetine (2 capsules of 60 mg each of Strattera®) were studied. Sample preparation included diluting acid hydrolysis followed by the native compound and metabolites extraction with chloroform from the saturated solution of ammonium sulfate at pH of 11-12. Thin-layer chromatography studies of the extracts were carried out in 18 mobile phases including those proposed by The International Association of Forensic Toxicologists for general drug screening, and those widely used in forensic toxicological studies. The color reactions were carried out using a range of chromogenic reagents. A Varian 1200 L mass spectrometer (Netherlands) equipped with a dual quadrupole mass analyzer was applied for analysis of the eluates from chromatograms. Identification was undertaken at the direct introduction of the sample into the ion chamber, electron-impact ionization (70 eV), and full ion scanning mode. Results. The spot of the native drug on the chromatogram was identified by the Rf, value. Two atomoxetine biotransformation products were identified by the molecular weights that correspond to the molecular ion peaks in the mass spectra. Conclusions. Atomoxetine and its biotransformation products were detected in the urine under TLC screening conditions and identified using mass spectrometry method. Chromatographic mobility of the native compound, hydroxyatomoxetine, and dihydroxyatomoxetine in the TLC screening systems as well as the results of their visualization using chromogenic reagents applied for toxicological drug screening in the systematic toxicological analysis have been determined.